ASSESSMENT OF THE MENTAL HEALTH OF TEACHERS OF A GENERAL SECONDARY EDUCATION INSTITUTION DURING THE TIME OF MARTIAL STATUS - Калиниченко, Ірина; Гончаренко, Світлана; Латіна, Ганна; Горєла, Тетяна (SWorldJournal, 2024)
In order to assess the psycho-emotional state and stress coping strategies of teachers in the conditions of martial law, 31 questionnaires of teachers aged 21-64 years of the Sumy institution of general secondary education of I-III degrees No. 15 were ana